Excess Capacity in Oligopoly with Sequential Entry - Luca Lambertini; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We analyse sequential entry in a quantity-setting oligopoly model. Firms have the option to adopt either a productive capacity which is optimal at the time of entry or a smaller one. This capacity may be suitable either for the steady state or just some time after entry. In the latter case firms never carry idle capacity, while in the former they keep spare capacity in the steady state. In the Cournot-Nash setting, a subgame perfect equilibrium may result in firms investing in capacity that will turn out to be idle later, depending on the size of the market and the rental price of capital. Older firms have larger spare capacity than later entrants and we can tell the age of a firm from its unused capacity. If market size is large enough, excess capacity turns out to be socially optimal.
Keywords: 330